(untitled) (Journal of Engineering, 2011)
Optimal design of three links and four links serial manipulator involves striking a balance between an appropriate link length, radius, link exact end effecter deflection and the amount of stress induced in each link. Optimization has been applied for getting a minimum robot weight through making the robot arm section tapered while keeping the first link as cylindrical tube as it represent the robot base only. The synthesis optimization problem involves setting up guess values for links length and radius subjected to constraints of deflection, stress and geometric constraints of total robot length. The optimization process focuses on minimization of robot weight as an objective function, the guess values has taken from three links manipulator and the industrial robot as four links serial manipulator. The results of optimization has been plotted and represented through the different relations between the design parameters (Link radius, length and total robot deflection, total robot weight, stress…etc). The results shows a good agreement minimizing the total deflection to(2x10-5 m) with this degree of precision an optimum design features may be obtained that gives a robot structure with high stiffness and minimum weight that enables the robot to do its tasks with minimum inertia effect.